2015
DOI: 10.1186/s12889-016-2800-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work stress and work ability among power supply workers in Guangdong, China: a cross-sectional study

Abstract: BackgroundFaced with the challenge of population aging, a prolonged working life is increasingly important in today’s society. Maintaining work ability of employees is one of the effective ways to cope with the challenges to sustainability of the workforce presented by population aging. Researchers have shown ongoing interest in exploring the determinants of restricted work ability. The aim of this study was to evaluate the effects of work stress on work ability among power supply workers in Guangdong, China.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 32 publications
3
32
1
1
Order By: Relevance
“…These results confirmed the expectations and are in agreement with the literature. Indeed, previous studies have already shown that various occupational factors, including violence, job stress, and organizational factors, can be associated with work ability impairment, both in nurses (Fischer & Martinez, 2013) and in other working activities (Khavanin et al, 2018; Li, Liu Z, Liu R, Li, & Lin, 2016). Negative work environments may influence the ability of nurses to provide optimal patient care (Oh, Uhm, & Yoon, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed the expectations and are in agreement with the literature. Indeed, previous studies have already shown that various occupational factors, including violence, job stress, and organizational factors, can be associated with work ability impairment, both in nurses (Fischer & Martinez, 2013) and in other working activities (Khavanin et al, 2018; Li, Liu Z, Liu R, Li, & Lin, 2016). Negative work environments may influence the ability of nurses to provide optimal patient care (Oh, Uhm, & Yoon, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have looked into associations between WAI and sick leave, disease (14-16), lifestyle (14,(17)(18), physical activity/exercise (19)(20), quality of life (3,(21)(22), age (23)(24)(25)(26), education (27), work-related stress (27)(28)(29)(30)(31), musculoskeletal disorders (32)(33)(34)(35), work-family conflicts (35), changing employer or leaving the profession (36)(37)(38), night and shift work (22,39), fatigue (40), current work ability (41)(42)(43), menopause (44), migration (45), ethnicity (46), physical work capacity (47), psychosocial hazard (48), successful aging strategies (26,(49)(50)(51), individual factors (4, 52-54), work-related factors, working conditions and workload (4,14,52,54), work injury (52), and job ...…”
mentioning
confidence: 99%
“…The ability to work (the physical and intellectual resources on which individuals can rely to respond to emotional, cognitive, and physical demands posed by their work [ 4 ]) decreases with age [ 5 , 6 , 7 , 8 , 9 ], especially for workers involved in more physically demanding jobs [ 3 , 4 , 5 , 10 , 11 ]. However, some resources, in particular the resources of an interpersonal nature (e.g., social support and team health climate), can sustain and protect the ability to work [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%